First record of Crypticerya brasiliensis (Hemiptera: Monophlebidae) on pequi trees (Caryocar brasiliense, Caryocaraceae) in the Brazilian Cerrado - de Castro, Marcelo Tavares; Montalvão, Sandro Coelho Linhares; Peronti, Ana Lucia Benfatti Gonzalez (Revista Ceres, 2025)
Crypticerya brasiliensis (Hempel, 1900) (Hemiptera: Monophlebidae) is a scale insect that has recently been observed in some native and exotic plants from the Brazilian Cerrado. This study reports for the first time the occurrence of C. brasiliensis in pequi trees (Caryocar brasiliense Camb., Caryocaraceae). Infestations were found in two pequi trees located in the urban area of ​​Brasília, Distrito Federal, Brazil. This is the first report of the occurrence of a monophlebid associated with the Caryocaraceae family.